ANALISIS POLA PERJALANAN DAN AKTIVITAS WISATAWAN INDONESIA MILENIAL KE SINGAPURA - Savira, Kiki; Suwena, I Ketut; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
Millennial recently became a trend in tourism. Millennials were born in 1980 to 2004, they grew up as digital natives, and have a consumptive nature where they do not hesitate to spend a certain amount of money to please themselves such as traveling, both at home and abroad. One of the countries that is a favorite destination for millennial Indonesian tourists when traveling abroad is Singapore. In addition to its close location, Singapore also has modern urban tourism attractions and technologies that match the millennial character. These facts became the background of this research; characteristics, travel patterns, and activities of millennial Indonesian tourists while traveling in Singapore. This research uses descriptive qualitative data analysis. The sample was determined purposively, totaling 105 millennial tourists from Indonesia who had traveled to Singapore. The data collection technique was done by using an online questionnaire. The results showed that the characteristics of millennial Indonesian tourists in Singapore were female, aged 21 to 25 years, unmarried, had a Bachelor's degree and were a private employee. Most tourists are first time traveling to Singapore, stay in Singapore 3 to 7 days, come and travel with family, arranging their own trips, using the internet as a source of information and mostly using MRT (Mass Rapid Transit) as a mode of transportation while traveling in Singapore. There are two millennial Indonesian tourists’ travel patterns while traveling in Singapore, which are chaining loop pattern, and base site pattern. The most common millennial Indonesian tourists’ activities in Singapore is doing culinary tourism (75%), the second is shopping (66%), and the third is enjoying local cultures (51%).